2017
DOI: 10.1371/journal.pone.0188705
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CD34+ cells and ALK5 signaling in the reconstruction of seminiferous tubule-like structures in 3-D re-aggregate culture of dissociated cells from neonatal mouse testes

Abstract: Tissue reconstruction in vitro can provide, if successful, a refined and simple system to analyze the underlying mechanisms that drive the morphogenesis and maintain the ordered structure. We have recently succeeded in reconstruction of seminiferous cord-like and tubule-like structures using 3-D re-aggregate culture of dissociated testicular cells. In testis formation, endothelial cells that migrated from mesonephroi to embryonic gonads have been shown to be critical for development of testis cords, but how en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…The first is that the proliferative capacity of ALCs was significantly higher than that of FLCs. Given that CD34 + cells show high proliferative activity and similar proliferative pattern to that of ALCs during re-aggregate culture 12 , these results indicate that our in vitro re-aggregate culture system reflects in vivo situations well; the proliferative activity of FLCs is high during the late fetal stage, but declines after birth 26 , 27 . On the other hand, ALCs arise from stem cells in the neonatal testis, and the precursor cells of ALCs proliferate and differentiate to 3β-HSD-positive LC progenitors (PLCs) 13 , 28 , 29 .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The first is that the proliferative capacity of ALCs was significantly higher than that of FLCs. Given that CD34 + cells show high proliferative activity and similar proliferative pattern to that of ALCs during re-aggregate culture 12 , these results indicate that our in vitro re-aggregate culture system reflects in vivo situations well; the proliferative activity of FLCs is high during the late fetal stage, but declines after birth 26 , 27 . On the other hand, ALCs arise from stem cells in the neonatal testis, and the precursor cells of ALCs proliferate and differentiate to 3β-HSD-positive LC progenitors (PLCs) 13 , 28 , 29 .…”
Section: Discussionmentioning
confidence: 53%
“…Dissociated testicular cells cultured inside a collagen matrix form within a week seminiferous tubule-like structures with lumen within which germ cells reside, and peritubular myoid cells (PMCs) attach around the SC-re-aggregates; outside the seminiferous tubule-like structures CD34 + cells form interstitial tissues within which LCs are localized. We have also shown the important roles of the interstitial tissues of the testis: testicular cells deprived of interstitial cells form dysmorphic structures, while re-addition of the interstitial cells restored tubule-like structures 12 .…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In order to investigate the behaviors and roles of CD34 + cells and PMCs in the reconstruction of seminiferous tubule-like structures, Abe et al [ 39 ] observed the behavior of CD34 + cells, p75 + cells, and PMCs in re-aggregate cultures. CD34 + cells, p75 + cells, and Sertoli cells initially exist as re-aggregates on their own, while most PMCs are distributed as single cells.…”
Section: Roles Of Interstitial Cells In the Reconstruction Of Testicu...mentioning
confidence: 99%